1955
DOI: 10.1002/cber.19550880119
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen über die Anwendbarkeit der Reduktionsmethode zur Bestimmung carboxylendständiger Aminosäuren in Peptiden und Proteinen

Abstract: Die in zwei vorhergehenden Mitteilungen beschriebene Methode der Bestimmung carboxylendsthdiger Aminosiiuren in Peptiden und Proteinen als DNP-Aminoalkohole wurde an zahlreichen synthetischen Peptiden und an Insulin a d ihre Brauchbarkeit untersucht. Die enielten Ausbeuten lngen im allgemeinen urn etwa 90 %, reduktive Spaltungen von Peptidbindungen wurden in keinem Falle beobachtet. Eine Anzahl von DNP-Aminoalkoholen wurde dargastellt und deren chmmatqpphische Trennung ausgearbeitet. Fur die h t i m m u n g ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1956
1956
1961
1961

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The more soluble fraction, procollagen, has apparently a very small number of N-terminal groups, and typical collagen has none unless it is degraded prior to analysis. On the other hand, Grassmann and co-workers (107,108,109) found an appreciable number of amino alcohols formed upon reduction; the yield amounted to about 5 per cent of all of the residues, or one thousand times the N-terminal residues of procollagen. Since the same amount was found with and without prior esterification, the authors concluded that these amino alcohols were derived from originally ester linked C-terminal amino acids, presumably involving the carbohydrate moiety of collagen.…”
Section: Structural Analysis Of Proteinsmentioning
confidence: 97%
See 4 more Smart Citations
“…The more soluble fraction, procollagen, has apparently a very small number of N-terminal groups, and typical collagen has none unless it is degraded prior to analysis. On the other hand, Grassmann and co-workers (107,108,109) found an appreciable number of amino alcohols formed upon reduction; the yield amounted to about 5 per cent of all of the residues, or one thousand times the N-terminal residues of procollagen. Since the same amount was found with and without prior esterification, the authors concluded that these amino alcohols were derived from originally ester linked C-terminal amino acids, presumably involving the carbohydrate moiety of collagen.…”
Section: Structural Analysis Of Proteinsmentioning
confidence: 97%
“…However, the latter reagent has been reinvestigated quite intensively by Grassmann and co-workers (107,108,109). Those authors conclude that no untoward reactions such as reduction of amide or peptide bonds occurs, even in several hours in boiling tetrahydrofuran; in contrast the results of Crawhall & Elliott indicate appreciable reduction of the amide bonds (110,111).…”
Section: Structural Analysis Of Proteinsmentioning
confidence: 99%
See 3 more Smart Citations